Functional Polyethylene Terephthalate with Nanometer‐Sized Bioactive Glass Coatings Stimulating In Vitro and In Vivo Osseointegration for Anterior Cruciate Ligament Reconstruction. Issue 5 (9th April 2014) - Li, Hong; Wu, Chengtie; Chang, Jiang; Ge, Yunshen; Chen, Shiyi
<x xml:space="preserve">Abstract</x> Polyethylene terephthalate (PET) artificial ligament has been widely used for treating serious cases of anterior cruciate ligament (ACL) injuries. However, the major drawback of PET artificial ligament is their insufficient surface bioactivity which hinders its osseointegration and mechanical anchorage in the bone tunnel. The aim of the present study is to prepare functional akermanite (AKT) nanocoatings on PET artificial ligaments by pulsed laser deposition (PLD) in order to promote the in vitro osteogenic differentiation of BMSCs and in vivo osteointegration. The results show that AKT glass nanocoatings on PET with uniform nanoparticles (around 30 nm) have been successfully prepared by PLD method. The in vitro study displays that the prepared AKT‐PET grafts support the attachment of BMSCs, and significantly stimulate the proliferation and osteogenic differentiation of BMSCs in comparison to pure PET grafts. AKT coatings on PET grafts promote the regeneration of new bone at the interface of the grafts and host bone tissues, and enhance the bonding strength in vivo as compared to pure PET grafts. The study establishes a viable method to apply PLD technique for preparing bioactive ceramic‐coated PET artificial ligaments with significantly improved osseointegration for ACL reconstruction.